2015
DOI: 10.1556/eujmi-d-14-00036
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bacteriuria among human immunodeficiency virus seropositive individuals in Osogbo, south-western Nigeria

Abstract: Human immunodeficiency virus-positive individuals are at increased risk of both asymptomatic and symptomatic urinary tract infections. The aim of this study was to determine the prevalence of asymptomatic bacteriuria (ASB) in HIV-positive individuals, its associated factors including any correlation with the CD4 count of the patient, and the antibiotic susceptibility pattern of the isolated organisms. Midstream urine and blood samples were collected from 242 consenting HIV-positive patients who were attending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 15 publications
1
21
1
Order By: Relevance
“…It has been observed that those with low lymphocyte CD4+ counts (<200 cell/μl) are at significantly higher risk of asymptomatic bacteriuria and are therefore more likely to develop urinary tract infection [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that those with low lymphocyte CD4+ counts (<200 cell/μl) are at significantly higher risk of asymptomatic bacteriuria and are therefore more likely to develop urinary tract infection [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Urinary tract infections, both symptomatic and asymptomatic, are serious public healthcare problems decreasing the quality of life and leading to work absence [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Urinary tract infections may be asymptomatic, acute, chronic, and complicated or uncomplicated, and the clinical manifestations of UTIs depend on the portion of the urinary tract involved, the etiologic organisms, the severity of the infection, and the patient's ability to mount an immune response to it. Both asymptomatic and symptomatic UTIs pose a serious threat to public health care, hence reducing the quality of life and resulting into work absenteeism [7]. The symptoms of UTIs such as fever, burning sensations while urinating, LAP, itching, formation of blisters and ulcers in the genital area, genital and suprapubic pain, and pyuria generally depend on the age of the person infected and the location of the urinary tract infected [2].…”
Section: Introductionmentioning
confidence: 99%
“…UTIs may occur either symptomatic or asymptomatic and the symptoms are either acute or chronic and may be uncomplicated or complicated. The clinical manifestation of urinary tract infections depends on; causative agent, severity of the bacterial infection and the ability to immune response (Olowe et al, 2015). Clinical symptoms of UTIs include; fever, burn during urinating, suprapubic pain and formation of blisters and ulcers in the genital area.…”
Section: Introductionmentioning
confidence: 99%